Effects of organic manures bioremediation on growth performance of Maize ( Zea mays L.) in crude oil polluted soil - Stella Obasi; Nwogo Obasi; Ephraim Nwankwo; Benneth Enemchukwu; Robert Igbolekwu; Jeff Nkama (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Crude oil pollution adversely affects the environment and its remediation presents significant challenge due to its complex nature. Bioremediation approaches have proved effective and the use of organic wastes makes the process eco-friendly. Therefore, this study investigated the effects of organic manures amendments of crude oil polluted soil on the growth and performance of maize (Zea mays L.) under potted environment at the botanic garden of University of Port-Harcourt, Nigeria.Method The loamy soils in different pots (5.0 kg each) were polluted with crude oil in six factorial treatments set (0.0%, 2.0%, 4.0%, 6.0%, 8.0% and 10.0%) and allowed for two weeks. Thereafter, the polluted soils were subjected to different organic manure amendment: poultry-manure, cow-dung, saw-dust, combined poultry-manure + cow-dung, combined poultry-manure + saw-dust and combined cow-dung + saw-dust manures with two sets of control: polluted soil + no organic manure and non-polluted soil + no organic manure. The amended soils were allowed for two weeks before sowing viable maize seeds and the seedling monitored every two weeks after germination for a period of eight weeks.Results Crude oil pollution impaired the maize seed germination, growth and development. Organic manures amendments of polluted-soil significantly improved (P < 0.05) maize plant agronomic characteristics with combined manures especially poultry-manure + cow-dung showing highest improvement than other combined or single manure treatment.Conclusion Combined organic manures amendments of crude oil polluted soil especially cow-dung + saw-dust were found to be environmentally friendly and beneficial for maize crop production.